Trends and Innovations in Character Building for Primary School Students in Indonesia - Bramianto Setiawan; Vina Iasha (PT. Pusmedia Group Indonesia, 2024)
Character education and many negative events are the focus of conversation in education today. This condition emphasizes the need to develop and strengthen character values in learning. A literature review is needed to understand more about character-building research. This research aims to provide an overview of the geographical distribution of publications, trends and learning innovations in student character building in elementary schools. This research uses the Systematic Literature Review (SLR) method with the Preferred Reporting Items for Systematic Reviews And Meta-Analysis (PRISMA) model. The search was conducted through the Google Scholar database with the keywords